Bibliometric analysis on use of apps and technologies in teaching separation processes at Chemical Engineering (Research, Society and Development, 2021)
The technological leverage challenges society to look for continuous improvement in their processes, whether in personal activities, economic or industrial. It is undeniable the aggregate value that technologies provide on a daily basis. In the teaching area, the use of digital technologies is still on an embryonic stage, since much of educational structures are rejecting its use because they do not know how to handle these transformations to validate the learning or to obtain students higher motivation and commitment. In the context of Engineering's learning, mainly in disciplines activities involving project and math calc, as unit operations and mixture separation processes of Chemical Engineering (subject with highly importance due to labor market and chemical industries’ productive processes), it is necessary to reformulate the theoretical structure of Universities to do a better use of digital tools, as simulation environments, virtual labs and mobile applications, in a project-based learning scenario, fostering the students proactivity and protagonism in search for knowledge, to transform the teacher in an advisor, a guide during the processes.